The Impact of Renewable Energy and Green Finance on SMEs Sustainability through Environmental Management Practices - Hariandy Hasbi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the mediating role of environmental management practices in the relationship between green finance, renewable energy adoption, and business sustainability among small and medium enterprises in Indonesia. The objectives are to assess the direct effects of green finance and renewable energy on business sustainability and to determine whether environmental management practices strengthen these effects. Data were collected from 200 small and medium enterprise respondents using a structured questionnaire. The green finance measurement instrument provides a validated framework specifically designed for small and medium enterprises. The results show that both green finance and renewable energy have significant positive effects on business sustainability. These effects become stronger when mediated by environmental management practices, including formal environmental policies, resource efficiency initiatives, and pollution control measures. Among the three dimensions of green finance, economic, environmental, and social, the economic dimension has the greatest impact, highlighting the importance of cost efficiency, green profitability, and return-oriented investments. The findings suggest that aligning financial and energy strategies with environmental management practices can lead to more meaningful and sustainable improvements in business performance.